Differential-Pulse Polarography Method for Evaluation of Diclofenac Sodium in Pharmaceuticals - Heba Y. Ahmed (Journal of Global Pharma Technology, 2018)
A reliable DPP process has been developed and applied for the estimation of Diclofenac sodium in pharmaceuticals form with DME versus Ag/AgCl. The best peak response was established a cathodic peak -1.14V in 0.002 M acetate buffer at pH5and 0.1M KCl as supporting electrolyte with four electrons transferred in irreversible process. To attain the highest sensitivity, instrumental and experimental and parameters were examined including the type and concentration of supporting electrolyte, pH, buffer solutions, pulse amplitude, and voltage step time. Diffusion current was in direct proportion to Diclofenac sodium concentration and with a linear relationship with the drug concentration in the range of (5 - 30 μg. mL-1) i.e. (1.57 × 10-5-9.4× 10-5 mol·L–1) with a correlation coefficient (r= 0.9993), detection limit (S/N = 3) was 0.85 μg. mL-1(i.e.2.67 × 10-6 mol·L–1) and the values of precision, in terms of RSD% ranged between 1.28- 4.11%.The established DPP methods offers excellent analytical figures of merits as well as applied to examine the commercial drug olfen capsule and Diclofenac sodium injection for the determination of Diclofenac sodium and found to be 99.8 mg, 76.9 mg compared to the stated value of 100mg and 75 mg respectively.Keywords: Differential-pulse polarography; Diclofenac sodium.